2013
DOI: 10.3390/cryst3010038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strain on Notched Zigzag Graphene Nanoribbons

Abstract: The combined effects of an asymmetric (square or V-shaped) notch and uniaxial strain are studied in a zigzag graphene nanoribbon (ZGNR) device using a generalized tight-binding model. The spin-polarization and conductance-gap properties, calculated within the Landauer-Büttiker formalism, were found to be tunable for uniaxial strain along the ribbon-length and ribbon-width for an ideal ZGNR and square (V-shaped) notched ZGNR systems. Uniaxial strain along the ribbon-width for strains ≥10% initiated significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It should be mentioned that edge defects of similar nature with the V-shaped GNR edge pattern features of the present work also have been studied broadly in the literature [42][43][44][45] , with the understanding that our work emphasizes on the formation of these GNR edge patterns as a result of pore-edge (and generally defect-edge) interactions. In particular, we mention that previous studies have also shown that an interplay of zigzag and armchair edges in GNRs may lead to significant changes in the electronic structure of the material 37,38 .…”
Section: Electronic Structure Of Gnrs With Patterned Edgesmentioning
confidence: 72%
“…It should be mentioned that edge defects of similar nature with the V-shaped GNR edge pattern features of the present work also have been studied broadly in the literature [42][43][44][45] , with the understanding that our work emphasizes on the formation of these GNR edge patterns as a result of pore-edge (and generally defect-edge) interactions. In particular, we mention that previous studies have also shown that an interplay of zigzag and armchair edges in GNRs may lead to significant changes in the electronic structure of the material 37,38 .…”
Section: Electronic Structure Of Gnrs With Patterned Edgesmentioning
confidence: 72%